2016
DOI: 10.1016/j.mad.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical sensor for the detection of multiple reactive oxygen and nitrogen species from ageing central nervous system homogenates

Abstract: Reactive oxygen and nitrogen species (ROS/RNS) have been widely implicated in the ageingThe free radical theory of ageing is one of the most prominent theories to explain the ageing process (Harman, 1956). This theory postulates that ageing and age-related diseases arise as a result of cumulative changes and/or damage to cells and tissues inflicted by reactive species. Under normal physiological conditions, redox homeostasis establishes a dynamic balance between pro-oxidants and antioxidants whereby the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Composite MWCNT microelectrodes (for details, see Fagan‐Murphy et al . ) were used for the detection of nitrite. Initially, the oxidation peak potential for nitrite was obtained using differential pulse voltammetry.…”
Section: Methodsmentioning
confidence: 99%
“…Composite MWCNT microelectrodes (for details, see Fagan‐Murphy et al . ) were used for the detection of nitrite. Initially, the oxidation peak potential for nitrite was obtained using differential pulse voltammetry.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the work of Dias et al . on nitrogen/oxygen species, Fagan‐Murphy et al . have very recently fabricated and applied a simple electrochemical sensor capable of simultaneously monitoring the production of hydrogen peroxide (H 2 O 2 ) and the reactive nitrogen species, peroxynitrite (ONOO − ), •NO and nitrite (NO 2 − ) from ageing central nervous system homogenates .…”
Section: Neurotransmitter Detection At Structurally Small Electrodesmentioning
confidence: 99%
“…The study found direct measurement of * NO concentration dynamics revealed a significant increase in the receptor peak in the triple transgenic mouse model at an early age, indicative of potential for extension into greater detailed studies. [48] Similar to the work of Dias et al on nitrogen/oxygen species, Fagan-Murphy et al [49] have very recently fabricated and applied a simple electrochemical sensor capable of simultaneously monitoring the production of hydrogen peroxide (H 2 O 2 ) and the reactive nitrogen species, peroxynitrite (ONOO À ), * NO and nitrite (NO 2 À ) from ageing central nervous system homogenates. [49] These electrodes were prepared by sealing individual carbon fibers (10 mm diameter) into pulledglass capillaries and the protruding carbon fibers were insulated by electrochemical deposition of poly(oxyphenylene), followed by dendritic platinum black.…”
Section: Nitrogeneous Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive oxidative stress is considered to be a key player in age‐related brain pathology. The break of equilibrium between reactive oxygen species (ROS) and endogenous antioxidant defenses in brain has been reported to induce dystrophy and death of neurons, ultimately leading to the degeneration of brain function (Fagan‐Murphy, Hachoumi, Yeoman, & Patel, 2016; Halliwell, 1992).…”
Section: Introductionmentioning
confidence: 99%